KELAYAKAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROYEK PADA MATERI BIOTEKNOLOGI UNTUK MENGUKUR KETERAMPILAN PEMECAHAN MASALAH DI SEKOLAH MENENGAH ATAS - Hidayat, Fiqri; Ningsih, Kurnia (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2026)
The Project-Based Student Worksheet (LKPD) serves as a learning medium intended to foster students’ critical and creative thinking abilities while enhancing their problem-solving competence through contextual project-based activities. This research aims to evaluate the feasibility of a project-based LKPD on biotechnology topics for assessing problem-solving skills among high school students. The study utilized a Research and Development (R&D) approach guided by the 4D model, which includes the define, design, and develop stages. Validation was carried out by six experts, including two university lecturers and four biology teachers, using an evaluation sheet that encompassed four criteria: content feasibility, language accuracy, presentation, and visual design. The validation results were analyzed using Aiken’s V for validity and the Intraclass Correlation Coefficient (ICC) to assess the reliability and consistency among the evaluators. Findings revealed that the developed LKPD achieved an average Aiken’s V score of 0.96, classified as valid, and an ICC reliability value of 0.820, indicating good reliability. Hence, the project-based LKPD developed in this study is deemed suitable for implementation as a learning resource to assess students’ problem-solving abilities in biotechnology at the senior high school level.